2010
DOI: 10.3390/ijerph7083071
|View full text |Cite
|
Sign up to set email alerts
|

The More the Worse: the Grade of Noise-Induced Hearing Loss Associates with the Severity of Tinnitus

Abstract: Tinnitus disturbs lives and negatively affects the quality of life of about 2% of the adult world population. Research has shown that the main cause of tinnitus is hearing loss. To analyze a possible association of the degree of hearing loss with the severity of tinnitus, we have performed a retrospective study using admission data on 531 patients suffering from chronic tinnitus. We have found that 83% of our tinnitus patients had a high frequency hearing loss corresponding to a noise-induced hearing loss (NIH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

16
88
1
7

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 116 publications
(112 citation statements)
references
References 14 publications
16
88
1
7
Order By: Relevance
“…Findings relate tinnitus severity to hearing loss at high frequencies (Weisz et al, 2004). Mazurek et al (2010) found a significant correlation between the degree of hearing loss and tinnitus loudness. They found that patients with decompensated chronic tinnitus had more hearing loss than those with compensated tinnitus.…”
Section: Introductionmentioning
confidence: 81%
See 2 more Smart Citations
“…Findings relate tinnitus severity to hearing loss at high frequencies (Weisz et al, 2004). Mazurek et al (2010) found a significant correlation between the degree of hearing loss and tinnitus loudness. They found that patients with decompensated chronic tinnitus had more hearing loss than those with compensated tinnitus.…”
Section: Introductionmentioning
confidence: 81%
“…Severe disabling tinnitus (SDT) is defined by Shulman as a symptom severe enough to disrupt the patient´s routine and to pre-vent him from performing his daily tasks. In 1953, Heller and Bergman (9) showed that over 90% of normal-hearing people reported tinnitus when placed in a soundproof cabin. However, the symptom did not cause any discomfort to those patients in daily life.…”
Section: Tinnitus In Otosclerosis Patientsmentioning
confidence: 99%
See 1 more Smart Citation
“…Noise is a common cause of cochlear damage leading to hearing loss or tinnitus [1][2][3] . The mechanism of noise-induced damage of the cochlea is a combination of mechanical and metabolic injuries.…”
Section: Introductionmentioning
confidence: 99%
“…The correlation reported between the severity of tinnitus and degree of accompanying hearing loss depends on the investigator [3,13] . In many cases, patients consider tinnitus to be even more disabling than hearing impairment, or they suffer from tinnitus without any discomfort or sense of hearing disturbance [14] .…”
Section: Introductionmentioning
confidence: 99%